Misconception Analysis in The Teaching Book of High School Physics and Edupark Mifan Waterpark and Geopark Ngarai Sianok in Dynamic Fluid Material - Dio Ade Putra; - Hamdi; Silvi Yulia Sari; - Hidayati; Dewi Puspa Sari (Universitas Negeri Padang, 2020)
The cause of errors and misconceptions experienced by some students and students is the large number of literature or books that describe the concept inappropriately. Writing difficult equations is also a factor in students' misunderstanding. So, misconceptions must be detected as soon as possible, especially in one of the causes, namely textbooks. This study aims to determine whether there are misconceptions in high school physics textbooks and physics edupark textbooks for class XI dynamic fluid material and to find out whether there are indications of other information that have the potential to cause misconceptions in textbooks.This research was a qualitative descriptive study that provides an interpretation of the data obtained rationally and objectively. In this study, data collection techniques were carried out by literature study and interviews with a team of physicists. The data source of this research was the physics textbook of Class XI high school by Marthen Kanginan in 2016 and the edupark physics textbook, while the data was the physics concept on dynamic fluid material. Credibility and triangulation techniques were used to determine the validity / validity of the data. Based on data analysis, conclusions can be drawn. Namely, there were misconceptions in book 2, while books 1 and 3 did not have any. Apart from misconceptions, the results of identification of other information were found, namely incomplete concepts, concepts that allow misconceptions, improving images, improving formulation writing, improving sentence writing, improving notation writing. The three books studied had the same findings of other information that led to misconceptions, namely on average there were 1 improvements for each indication found